Delayed catabolism of high density lipoprotein apolipoproteins A-I and A-II in human cholesteryl ester transfer protein deficiency. - Ikewaki, K (1993)
Deficiency of the cholesteryl ester transfer protein (CETP) in humans is characterized by markedly elevated plasma concentrations of HDL cholesterol and apoA-I. To assess the metabolism of HDL apolipoproteins in CETP deficiency, in vivo apolipoprotein kinetic studies were performed using endogenous and exogenous labeling techniques in two unrelated homozygotes with CETP deficiency, one heterozygote, and four control subjects. All study subjects were administered 13C6-labeled phenylalanine by primed constant infusion for up to 16 h. The fractional synthetic rates (FSRs) of apoA-I in two homozygotes with CETP deficiency (0.135, 0.134/d) were found to be significantly lower than those in controls (0.196 +/- 0.041/d, P < 0.01). Delayed apoA-I catabolism was confirmed by an exogenous radiotracer study in one CETP-deficient homozygote, in whom the fractional catabolic rate of 125I-apoA-I was 0.139/d (normal 0.216 +/- 0.018/d). The FSRs of apoA-II were also significantly lower in the homozygous CETP-deficient subjects (0.104, 0.112/d) than in the controls (0.170 +/- 0.023/d, P < 0.01). The production rates of apoA-I and apoA-II were normal in both homozygous CETP-deficient subjects. The turnover of apoA-I and apoA-II was substantially slower in both HDL2 and HDL3 in the CETP-deficient homozygotes than in controls. The kinetics of apoA-I and apoA-II in the CETP-deficient heterozygote were not different from those in controls. These data establish that homozygous CETP deficiency causes markedly delayed catabolism of apoA-I and apoA-II without affecting the production rates of these apolipoproteins.